Factors Affecting the Compliance of Motor Vehicle Taxpayers in Medan City - Haya Fadiyah Hanin; Juliana Nasution; Yenni Samri Juliati Nasution (Green Publisher Indonesia, 2024)
This research is to determine the factors that influence taxpayer compliance in paying taxes. The variables are the tax whitening program, mobile Samsat service, drive thru Samsat service, and e-Samsat program as independent variables and taxpayer compliance as the dependent variable. The population in this study were all taxpayers registered with SAMSAT Medan City, totaling 2,724,585 motorized vehicles with a sample of 100 people. This research uses a questionnaire as a research instrument, prepared using a Likert scale and then analyzed using a multiple regression process with SPSS. The results obtained are that the tax whitening program and mobile Samsat services have no effect on taxpayer compliance. Meanwhile, the Samsat drive thru and e-Samsat programs have a significant positive effect on taxpayer compliance. This research is expected to increase insight and enrich knowledge about the factors that influence taxpayer compliance. It is also hoped that the results of this research can be used by the tax office as consideration in formulating tax policies that focus on increasing taxpayer compliance.